DESAIN PENCAHAYAAN PADA RUANG KELAS SMA NEGRI 9 SURABAYA - Budiman, Linda; Indrani, Hedy C. (Institute of Research and Community Outreach - Petra Christian University, 2012)
A classroom functions as a place for learning and teaching activities. To accommodate these funcions, it is important to consider the lighting quality that should meet the standard requirement for the learning activities. Initial measurements of the light intensity of the classrooms in SMA Negri 9 Surabaya show that some of these classrooms have not met the standard requirement. This research used the Dialux v. 4.8 software to investigate and discover the best lighting quality that should be achieved according to ligthing standards. Results show that the type of lamp used influences the lighting conditions of a classroom. Meanwhile different interior elements, furniture materials and finishings also affect the distribution of light which produce different light reflections that influence the comfort level of the users. The use of colour on the interior elements and furnitures also affect the light intensity in which every colour produces different light reflections and interior atmoshphere.